PENGARUH PENGGUNAAN MEDIA VIDEO ANIMASI TERHADAP HASIL BELAJAR IPAS SISWA KELAS III SDN 79 BONGKI BONGKI KAB. SINJAI - Esong Mappalolang; Rafiah Mahmudah; Syarifah Aeni Rahman (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was conducted because the science and social studies learning outcomes of third-grade students at SDN 79 Bongki-Bongki were considered still low. This motivated the researcher to seek a solution by applying animated video media. The main objective of this study was to examine the extent to which this media could improve students’ learning outcomes. This research used a pre-experimental method with a one-group pretest-posttest design and was carried out over four meetings. The sample consisted of 18 students selected using a saturated sampling technique. The instrument used was a learning achievement test consisting of 15 items, administered before and after the treatment. The results showed that the average pretest score was 52.61, while the average posttest score increased to 78.56. Based on the paired sample t-test, a significance value of 0.000 < 0.05 was obtained, indicating that the use of animated video media had a significant effect on students’ science and social studies learning outcomes. Animated video media was proven effective in helping students understand abstract material in a more concrete and engaging way.